Implementation of the Pancasila Student Profile Strengthening Project (P5) in Elementary School - Yuriska Dewi Suwarno Putri; Anis Khaerunisah; Dewi Astuti; Septiana Septiana; Tina Alfiani; Zaqiyatul Fakhiroh; Almaida Ayunda Febrianti (PT. Pusmedia Group Indonesia, 2023)
The learning process at SD Negeri Kebon Baru 1 has implemented an independent curriculum and Pancasila student profile. In realizing the Pancasila student profile, SD Negeri Kebon Baru 1 carried out the Strengthening of the Pancasila Student Profile Project (P5). In learning, the teacher explains the material with a predetermined theme. To produce a project, teachers and students can create products that match the theme that has been chosen. With the learning activities of Strengthening the Pancasila Student Profile Project (P5), it is hoped that it can develop creativity in accordance with the elements in the Strengthening of the Pancasila Student Profile Project (P5) dimension, one of which is in the creative dimension . This study aims to find out and describe how the implementation of the project to strengthen the profile of Pancasila students in SD Negeri Kebon Baru 1 Cirebon City. This research uses qualitative methods with a descriptive approach, collecting data through observations, interviews, and documentation. The subjects of this study were homeroom teachers and some grade 4 students. The data analysis technique used in this study is a qualitative descriptive method that is by looking for, collect, and organize systematically. The results of this study show that the implementation of the Pancasila student profile (P 5) strengthening the project in SD Negeri Kebon Baru 1 Cirebon City is very good because in P5 activities teachers have been very well prepared and planned activities. Teachers provide opportunities for students to develop students' creativity to produce a project. The theme taken in the P5 activity at SD Negeri Kebon Baru 1 is